(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Diabetic macular edema is one of the leading causes of visual acuity loss in people with diabetes. It produces blurry vision, particularly in the centre of the vision field, floaters and black spots in front of the eyes etc. The treatment recommended by modern science is laser photocoagulation and anti-VEGF injection, which is pricey and does not ensure visual reversal in the patient. In Ayurveda text, diabetic retinopathy and diabetic macular edema are not directly described but etiopathogenesis of eye diseases and Prameha gives an idea of possible correlation between these two diseases. So, DME resembles Timira (Pramehajanya). In Ayurveda, Timira has been explained in detail by our Acharyas. Clinical manifestations of Timira are Vihwal Drishti (blurred vision), Makshika Mashaka Kesha Jaala Pashyati (floaters), Tamasa Darshanam (Scotoma- black spots in front of eyes) and Nasa Akshi Yuktani Vipritani Vikshate (Metamorphopsia or distorted vision) which has similarity with features of DME. Material & Methods: In the present study, a female patient aged 51 years, visited the Shalakya Tantra OPD of National Institute of Ayurveda, Jaipur, with complaining of Blurriness of vision since 6 months and uncontrolled blood sugar level. Result: Blood sugar level was controlled and saw reduction in subjective and objective parameters. Discussion: Following an Ayurvedic drugs and routine will assist to slow the advancement of the condition, prevent further diabetes complications, and improve quality of life.